Hemoglobin Level Examination And Anemia Handling Efforts In Adolescents In BPPT Darus Sholah Jember Senior High School - Aini, Elfira Nurul (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2020)
Anemia is a nutritional problem that affects millions of people in developing countries and remains a major challenge to human health. Based on the hemoglobin examination according to Manuaba (2007) the classification of anemia is not anemia (Hb 12.00 gr), mild anemia (Hb 9.00-11.00 gr), moderate anemia (Hb 7.00-8.00 gr ) and severe anemia (Hb less than 7.00 gr). Anemia in Jember Regency, especially among students, is still quite high, namely from a total of more than 76 thousand students, 41 percent of them have anemia. Efforts to increase Hb levels are to consume foods rich in iron, one of which is date juice. This activity aims to screen and treat anemia in young women. The target is young women in class X and XI in the BPPT Darus Sholah Superior Senior High School, Jember Regency. The method used is to provide health education and provide date palm extract. The results obtained were 70percent of the target had an increase in hb levels with an increase in average hb levels of 1.2 gr.